Optimizing the Role of Students in Reducing Stunting in North Musi Rawas Regency: Optimalisasi Peran Mahasiswa Dalam Upaya Penurunan Stunting Di Kabupaten Musi Rawas Utara - Nenny Wahyuni; Misnaniarti Misnaniarti; Hasyim Hamzah; Nur Alam Fajar; Annisa Rahmawati; Muhammad Amin Arigo Saci; Indah Yuliana; Laura Dwi Pratiwi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
North Musi Rawas Regency, based on the results of the 2021 SSGI, is in 5th place for the Regency with the highest stunted toddler prevalence in South Sumatra, which is 28.3%. The results of the situation analysis based on PK21 data show that 12.8% of people there are at high risk of experiencing stunting. One of the efforts that can be made to accelerate the reduction of stunting rates is through university assistance. By the mandate of Presidential Regulation Number 72 of 2021, Musi Rawas University assists in the form of family assistance. This program has carried out by students for one month using counseling and mediation methods. The education provided is in the form of sensitive interventions, including environmental hygiene, using healthy latrines, the importance of clean and healthy water sources, and the importance of parenting patterns in the family. This mentoring activity increased 15% number of visits by toddlers to posyandu, which means that the community is starting to understand the importance of routinely monitoring children's health to prevent stunting